Public relations strategy in improving the image of service quality at let's stop vegetarian Medan - Metta Walia; Weny, Weny (Paspama Institute, 2024)
The outbreak of Covid-19 is currently hitting almost all parts of the world. These conditions have had various negative impacts on human life both in the political, economic and educational sectors, in particular experiencing such a large impact. This research was made with the aim of knowing the positive image of the Public Relations Strategy. In addition, this research is also intended to contribute to the development of Mari Mampir Vegetarian Medan. research conducted from the point of view of society or one's way of observing phenomena around them. This study uses the constructivism paradigm because it seeks to understand the processes and social interactions that occur between human practitioners. This research method is descriptive research with a qualitative approach. Data collection was carried out by observation and interview techniques. Researchers use source triangulation to check the validity of research data. Data analysis in this study uses 3 components, namely data reduction, data presentation, and drawing conclusions.